2000
DOI: 10.1055/s-2000-7338
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Evaluation of Rat Peripheral Nerve Repair With End-to-Side Neurorrhaphy

Abstract: This study was designed to assess long-term reinnervation of end-to-side neurorrhaphy in the rat. The cut right peroneal nerve was repaired and sutured to the side of the intact tibial nerve. Both the extent of reinnervation and the integrity of the intact donor nerve were evaluated in 48 Sprague-Dawley rats randomly treated with fresh or delayed nerve repair with or without perineurotomy. Evaluations included nerve conduction velocity (NCV) of both the peroneal and tibial nerves, dry muscle weight, and histol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
44
0
2

Year Published

2005
2005
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 70 publications
(49 citation statements)
references
References 30 publications
3
44
0
2
Order By: Relevance
“…71 Accordingly, the structure and function of muscles innervated by the donor nerve and the donor nerve itself completely recovered at 6-12 months after surgery. 53,66,69,72,73 Together, these observations support the view that end-to-side nerve coaptation has no major detrimental long-term effect on the donor nerve. This is in accordance with two recent reports of clinical case series, 18,22 in which none of patients had any sensory or motor loss in the innervation zone of the donor nerve, even though perineurial sutures were made after the creation of a perineurial window in the donor nerve.…”
supporting
confidence: 75%
See 2 more Smart Citations
“…71 Accordingly, the structure and function of muscles innervated by the donor nerve and the donor nerve itself completely recovered at 6-12 months after surgery. 53,66,69,72,73 Together, these observations support the view that end-to-side nerve coaptation has no major detrimental long-term effect on the donor nerve. This is in accordance with two recent reports of clinical case series, 18,22 in which none of patients had any sensory or motor loss in the innervation zone of the donor nerve, even though perineurial sutures were made after the creation of a perineurial window in the donor nerve.…”
supporting
confidence: 75%
“…12,13,29,[48][49][50]54 but not later from 4 up to 8 months after surgery. 16,51,53,64 Interestingly, if epineurial or perineurial windows were enlarged from 1 to 4 or 5 mm, respectively, then, also, the magnitude of axonal ingrowth into the recipient nerve was increased. 65,66 Subepineurial focal degeneration and demyelination of the donor nerve distal to the site of coaptation in experimental groups Notably, bimodality coefficient > 0.555 indicates that a distribution is bimodal 56 (but see Jackson, P.R., Tucker, G.T., and Woods, H.F. (1989).…”
Section: Kovač Ič Et Almentioning
confidence: 99%
See 1 more Smart Citation
“…The use of the fibular nerve in studies of nerve regeneration was boosted after the reintroduction of the end-to-side neurorrhaphy 1,2,3,4,5,6,7,8,9,10,11,23,13 . We were not able to find many references to the unmyelinated axons of the fibular nerve in these and other recent studies.…”
mentioning
confidence: 99%
“…In fact, when there is no injury to the donor nerve, nerve regeneration can occur following endto-side anastomosis, but several experimental studies have shown that when the donor nerve had a fenestration, the effect of nerve regeneration was better [71][72][73][74]. Although there are still controversies over whether fenestration can damage the donor nerve, many studies have confirmed that the fenestration of the epineurium can cause a slight damage to the donor nerve, but does not affect the donor nerve function [75][76][77]. this approach does not cost the donor function when nerve grafting.…”
Section: Epineurium or Perineurium Windowmentioning
confidence: 99%